2016
DOI: 10.1038/srep20139
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of cellular decisions in collective behavior: Implications for wound healing

Abstract: Collective processes such as wound re-epithelialization result from the integration of individual cellular decisions. To determine which individual cell behaviors represent the most promising targets to engineer re-epithelialization, we examined collective and individual responses of HaCaT keratinocytes seeded upon polyacrylamide gels of three stiffnesses (1, 30, and 100 kPa) and treated with a range of epidermal growth factor (EGF) doses. Wound closure was found to increase with substrate stiffness, but was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…As one application example of the COSDIENT, the wound healing assay with the immortalized human skin keratinocytes was performed not only to investigate the stiffness effect on the cellular behaviors but also to verify the usefulness of the COSDIENT. Previous studies have already investigated the stiffness effect on the keratinocytes wound healing using the individual stiffness platforms made of polydimethylsiloxane and polyacrylamide, which showed that the wound healing speed was faster on the stiff substrate compared with the softer one (Kim et al, ; Wang, Wang, et al, ; Wickert, Pomerenke, Mitchell, Masters, & Kreeger, ). As a first attempt on the collagen‐based substrate, the COSDIENT exhibited that the wound coverage by the keratinocytes was faster on the stiff region than on the softer regions, which was the same trend observed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one application example of the COSDIENT, the wound healing assay with the immortalized human skin keratinocytes was performed not only to investigate the stiffness effect on the cellular behaviors but also to verify the usefulness of the COSDIENT. Previous studies have already investigated the stiffness effect on the keratinocytes wound healing using the individual stiffness platforms made of polydimethylsiloxane and polyacrylamide, which showed that the wound healing speed was faster on the stiff substrate compared with the softer one (Kim et al, ; Wang, Wang, et al, ; Wickert, Pomerenke, Mitchell, Masters, & Kreeger, ). As a first attempt on the collagen‐based substrate, the COSDIENT exhibited that the wound coverage by the keratinocytes was faster on the stiff region than on the softer regions, which was the same trend observed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The stiffness gradient of the COSDIENT further showed the continuous increase of the wound healing with the increase of the stiffness that was not previously shown. Various possibilities, such as increased migration speed by epithelial‐mesenchymal transition and higher cell spreading and proliferation rate, have been demonstrated to promote the wound healing, but the underlying mechanism remains unclear (Kim, Gweon, et al, ; Wang, Wang, et al, ; Wickert et al, ). Thus, the COSDIENT would be a good platform to examine the stiffness effect on the promotion of cell migration trend depending on the stiffness change on a single substrate.…”
Section: Discussionmentioning
confidence: 99%
“…EGF improves the migration and proliferation of fibroblasts and keratinocytes, and is also involved in wound closure events, such as reepithelialization . Exogenous EGF treatment can enhance radiation‐induced wound repair while preserving tissue stability .…”
Section: Discussionmentioning
confidence: 99%
“…EGF is a polypeptide hormone, which is involved in the regulation of a wide variety of physiological and pathological process, including growth, tissue repair, regeneration, and neoplasia . EGF also participates in wound closure events, including reepithelialization, by improving keratinocyte migration and proliferation . CLASP2 has not been studied as a wound healing agent in vitro or in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In essence, cells treated with soluble EGF appeared to be engaged in a game of bumper cars, and cells exposed to immobilized EGF traveled on a laned highway and more efficiently closed the wound. Although collective migration into a wound can result from multiple single‐cell behaviors, our recent analysis also highlighted the key role of persistence in determining the extent of wound closure when cells are exposed to both mechanical and growth factor cues (53). Thus, the collection of single‐cell data may be particularly important in examining differences between soluble and immobilized growth factor delivery, as measurement of only collective outcomes ( e.g.…”
Section: Discussionmentioning
confidence: 99%